Streetwise Children. Bambini e metropoli da Dickens a Lethem - Silvia Albertazzi (Ricerche di Pedagogia e Didattica, 2017)
The aim of my essay is to compare two novels – an English classic, and a contemporary American work – whose main characters have to face and negotiate the metropolitan spaces alone since their childhood. By analyzing how David Copperfield in Charles Dickens’s eponymous novel and Dylan Ebdus in Jonathan Lethem’s The Fortress of Solitude learn to know the city and to leave in it, I will also show the Dickensian elements to be found in the novel of the American author, who defines himself “a follower of Dickens”.